Carl Johan Petersson; Reindeer herd production - a modelling approach - Skjenneberg (ed.), Sven (Rangifer, 1993)
Carl Johan Petersson defended his AgrD thesis at the Swedish University of Agricultural Sciences, Uppsala, Sweden, on December 17, 1993.